The Effectivenes of Scrabble Game for Studentsâ€™ Spelling Mastery in Vocabulary Learning for Seventh Graders of Smp Muhammadiyah Surabaya - Heru Suprayogi (Tell : Teaching of English Language and Literature Journal, 2016)
The analysis of â€œThe Effectiveness of Scrabble Game For Studentsâ€™ Spelling Mastery In Vocabulary Learningâ€ is still difficult to find. The researcher formulates the statement of the research, scrabble game is effective for studentsâ€™ spelling mastery in vocabulary learning. The objective of the research is to find out whether scrabble game is effective for stdentsâ€™ spelling mastery. This research uses experimental design, with the hypothesis there is difference in spelling mastery of seventh graders taught by scrabble game and who are not. The subjects are seventh graders students of SMP Muhammadiyah 6 Surabaya where VIID as experimental class and VIIC as control class. Data colection technique uses test, pre-test and post test. The score pre-test and post test are compared to count the difference. The pre-test and post test score are counted using SPSS 1.6 Software to know the significant different. The counting result shows the Ï-value is 0,000 for the experiment class. Meanwhile the Eta square result is 0,41 that means the treatment gives large effect. It proves that the scrabble game is effective for studentâ€™s spelling mastery.